MAGISTRACY IN MODERN RUSSIAN UNIVERSITY: REGIONAL DIMENSION - Artur G. Kazharov; Khazhismel G. Tkhagapsoev; Martin M. Yakhutlov (Высшее образование в России)
The article analyzes the features and problems of magistracy development in the regional university on the example of Kabardino-Balkarian State University. It is noted that the problems of development of a regional university in modern Russia are most clearly manifested at realization of the master's training. The authors raise the question about a need to adjust the strategy of development of domestic education, particularly, about the expansion of the powers of a regional university for the implementation of various models of master's training and about the effective language policy in education.